AB0559 Reliability and Validity of The Turkish Translation of The Beliefs about Medicines Questionnaire (BMQ-T) in Patients with Behçet's Disease. (15th July 2016) - Cinar, M.; Cinar, F.I.; Acikel, C.; Yilmaz, S.; Cakar, M.; Horne, R.; Simsek, I.
Abstract : Background: Behçet's disease (BD) is a multisystem vasculitis with unknown etiology characterized by the heterogeneous nature of organ involvement and a fluctuating disease course. There are various effective treatment alternatives, while, the first and essential step for a successful treatment is patients' adherence to therapy. Efforts to improve treatment outcomes require a better understanding of the particular barriers to and facilitators of adherence to therapy, and of patient experiences of taking treatment. Treatment adherence is influenced by many factors, among them: i) route of administration, ii) psychosocial factors, iii) fear of side effects, iv) lack of an immediate feeling of benefit, and v) patient attitudes to health and disease and beliefs about medicines. Objectives: The aim of this study was to evaluate the reliability and validity of the Turkish translation of the Beliefs about Medicines Questionnaire (BMQ-T) © for patients with Behçet's disease. Methods: This methodological study enrolled a sample of 125 patients. The scale was adapted to Turkish through a process including translation, comparison with versions in other languages, back translation, and pretesting. Construct validity was evaluated by factor analysis. Medication adherence evaluated as poor, moderate and good according to the Morisky Medication Adherence Scale (MMAS). BMQ-T scores compared along medication adherence status groups. Results: In our study, as in the original scale, the factor analysis confirmed that the BMQ-T had a four-factor structure explaining 54.73% of the total variance. The BMQ-T had acceptable internal consistency (Cronbach's alpha coefficient: Specific Necessity = 0.812; Specific Concerns = 0.672; General Harm = 0.677; General Overuse = 0.656), adequate test–retest reliability (intraclass correlation coefficients: Specific Necessity = 0.715; Specific Concerns = 0.680; General Harm = 0.678; General Overuse = 0.327). Specific Necessity and Specific Concerns scores were significantly different between medication adherence status groups. Conclusions: The psychometric properties of the BMQ-T were consistent with those reported in the original study. The BMQ-T was found to be a valid and reliable tool for evaluating beliefs about medicines in patients with Behçet's disease. © Professor Rob Horne. References: Horne R, Weinman J, Hankins M. The Beliefs about Medicines Questionnaire: the development and evaluation of a new method for assessing the cognitive representation of medication. Psychol Health 1999;14:1–24. Disclosure of Interest: None declared